Deep Learning dalam Meningkatkan Mutu Pembelajaran PAI di SMP Kabupaten Sumedang: Studi Kasus di SMP Plus Tanjungsari - Supian Munawar; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Penerbit Widina, Widina Media Utama, 2026)
The quality of Islamic Religious Education (PAI) learning at the junior high school level is often limited to a rote approach (surface learning), thus less encouraging internalization of values and changes in student behavior. Deep learning offers an alternative approach that focuses on in-depth understanding, reflection, and contextual relevance. However, its implementation is often hampered by poorly integrated management factors. This study aims to investigate how the integration of the learning management function (POAC) with deep learning pedagogy can improve the quality of PAI learning in junior high schools. The study used a qualitative approach with a case study design at SMP Plus Tanjungsari, Sumedang. Data were collected through in-depth interviews with the principal and PAI teachers, participant observation, and document study, then analyzed interactively. The implementation of deep learning integrated with the POAC function has been proven to improve the quality of PAI learning holistically. Participatory planning resulted in a Deep Learning Plan (RPM), effective organization through PAI teams and student differentiation, student-centered implementation with active and contextual methods, and comprehensive evaluation covering cognitive, affective, and spiritual aspects. Supporting factors such as the principal's instructional leadership and a flexible curriculum reinforced this success. Improving the quality of Islamic Religious Education (PAI) learning requires synergy between a deep learning pedagogical approach and a structured management framework. The resulting integrative model can serve as a reference for other schools in implementing meaningful and transformative learning.ABSTRAKMutu pembelajaran Pendidikan Agama Islam (PAI) di tingkat SMP masih sering terbatas pada pendekatan hafalan (surface learning), sehingga kurang mendorong internalisasi nilai dan perubahan perilaku siswa. Deep learning menawarkan pendekatan alternatif yang berfokus pada pemahaman mendalam, refleksi, dan keterkaitan kontekstual. Namun, implementasinya sering terkendala oleh faktor manajemen yang kurang terintegrasi. Penelitian ini bertujuan untuk menyelidiki bagaimana integrasi antara fungsi manajemen pembelajaran (POAC) dengan pedagogi deep learning dapat meningkatkan mutu pembelajaran PAI di SMP Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus di SMP Plus Tanjungsari, Sumedang. Data dikumpulkan melalui wawancara mendalam dengan kepala sekolah dan guru PAI, observasi partisipatif, dan studi dokumen, kemudian dianalisis secara interaktif. Implementasi deep learning yang terintegrasi dengan fungsi POAC terbukti meningkatkan mutu pembelajaran PAI secara holistik. Perencanaan partisipatif menghasilkan Rencana Pembelajaran Mendalam (RPM), pengorganisasian efektif melalui tim PAI dan diferensiasi siswa, pelaksanaan berpusat pada siswa dengan metode aktif dan kontekstual, serta evaluasi komprehensif yang mencakup aspek kognitif, afektif, dan spiritual. Faktor pendukung seperti kepemimpinan instruksional kepala sekolah dan kurikulum fleksibel memperkuat keberhasilan ini. Peningkatan mutu pembelajaran PAI memerlukan sinergi antara pendekatan pedagogis deep learning dan kerangka manajemen yang terstruktur. Model integratif yang dihasilkan dapat menjadi rujukan bagi sekolah lain dalam mengimplementasikan pembelajaran yang bermakna dan transformatif.